Registration of 3D Spatial Objects for 3D Cadastre - Ahmad Nasruddin, Mohd. Hasif (2007)
This paper presents a research work to develop a 3D land registration system for 3D cadastre objects. In general, current 2D land registration is managed separately by two agencies, i.e. Land Offices (LO) and Department of Survey and Mapping Malaysia (DSMM). Each agency has their own registration system, namely, Computerized Land Registration System (CLRS) and Digital Cadastral Database (DCDB) respectively. Previous research revealed the drawbacks of existing registration system especially on 3D cadastral objects, and obviously this situation has to be tackled if a full 3D registration needs to be realized. This 3D cadastre registration will serve as a first attempt to develop a more complete system. The main idea of the work is to combine the two databases i.e. CLRS and DCDB. The work also aims to enhance current registration system especially for 3D objects e.g. buildings. This paper attempts to elaborate on developed schema for the combine CLRS and DCDB database and focus on the aspect of 3D registration for 3D objects. The design of the registration system will be presented i.e. the conceptual and the logical model. The output from the experiment will be highlighted, i.e. database queries of the 3D objects and incorporated with a simple GUI.